Asymmetrically modified graphene for lubricating oil and method for preparing the same

CN122941477APending Publication Date: 2026-10-20WENZHOU LIANKE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610922075.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但是,氧化石墨烯的水分散液的粘度较高,无法在高固含量的前提下得到流动性良好的分散体系,想把足够的氧化石墨烯加入油相中会引入大量的水,会后续除水增加难度

Benefits of technology

1、通过先构建氧化石墨烯悬浊液体系,再加入少量水形成油包水乳液,使氧化石墨烯进入油/水界面,实现氧化石墨烯分散,同时为改性反应提供可能,该方法避免了大量水的加入,并得到高固含量的产物,有利于生产和应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application discloses an asymmetric modified graphene for lubricating oil and its preparation method, belonging to the technical field of lubricating oil additives. The preparation method includes the following steps: S1, mixing graphene oxide powder, an oily dispersant, an oleophilic modifier, and a base oil, emulsifying and dispersing (I), and maintaining the temperature to obtain a graphene oxide suspension; S2, mixing a mixture containing water, a hydrophilic modifier, and a cosolvent with the suspension, emulsifying and dispersing (II), heating, and reacting to obtain a slurry containing asymmetric modified graphene. The obtained asymmetric modified graphene has better anti-wear and friction-reducing properties, prevents oil burning, and is almost not adsorbed by oil filters. Furthermore, the preparation process is simple, highly feasible, and beneficial for production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to an asymmetric modified graphene for lubricating oil and its preparation method, belonging to the field of lubricating oil additive technology. Background Technology

[0002] Currently, adding graphene can alleviate oil consumption to some extent, but this problem gradually reappears later in the oil's lifespan. Similarly, while graphene initially improves anti-wear and friction-reducing properties, this effect diminishes significantly over time. Furthermore, engine oil filters remove impurities and dirt from the oil, providing clean and reliable lubricating oil to reduce wear and extend engine life. However, graphene is also filtered out by the oil filter, causing its content in the oil to gradually decrease with mileage. Reducing the graphene size can increase filter paper permeability, but some graphene will still adhere to the filter paper, failing to completely solve the problem. Additionally, reducing graphene size incurs higher manufacturing costs.

[0003] Experiments have shown that modified graphene obtained by grafting graphene oxide significantly improves the permeability of filter paper. However, modifying graphene oxide for application in lubricating oils presents challenges. Firstly, graphene oxide is hydrophilic and cannot be stably dispersed in lubricating oils; its application requires modification to become lipophilic, necessitating the use of oil-soluble modifiers. The modification process must be carried out in oily solvents, but graphene oxide is poorly dispersed in these solvents, significantly reducing preparation efficiency and effectiveness. Secondly, an aqueous dispersion of graphene oxide can be added to the oil phase to achieve the modification reaction, followed by water removal. However, the viscosity of the aqueous dispersion of graphene oxide is high, making it difficult to obtain a well-flowing dispersion system with high solids content. Adding sufficient graphene oxide to the oil phase introduces a large amount of water, increasing the difficulty of subsequent water removal. In addition, the modified graphene obtained by traditional modification methods is bifacially symmetrically modified. The wear resistance and friction reduction properties of this bifacially symmetrically modified graphene are lower than those of unmodified graphene, meaning that although the filter paper permeability is improved, the wear resistance and friction reduction properties are reduced. Summary of the Invention

[0004] To address the aforementioned technical problems, this application provides an asymmetric modified graphene for lubricating oil and its preparation method.

[0005] According to a first aspect of this application, a method for preparing asymmetric modified graphene for lubricating oil is provided.

[0006] A method for preparing asymmetric modified graphene for lubricating oil, the method comprising the following steps: S1. Mix graphene oxide powder, oily dispersant, lipophilic modifier and base oil, emulsify and disperse I, keep warm to obtain graphene oxide suspension; S2. A mixture containing water, a hydrophilic modifier, and a co-solvent is mixed with a suspension, emulsified and dispersed (II), heated, and reacted to obtain a slurry containing asymmetric modified graphene.

[0007] Optionally, in step S1, the oily dispersant is selected from at least one of Span 80, boronized polyisobutylene succinimide, isopropyl titanate, sorbitan oleate, polyether, stearic acid, oleic acid, and tallow amine polyoxyethylene ether.

[0008] Optionally, in step S1, the lipophilic modifier is selected from at least one of tallow amine, polyisobutylene amine, polyisobutylene succinimide, butyl diphenylamine, octyl diphenylamine, nonyl diphenylamine, and N-phenyl-1-naphthylamine.

[0009] Optionally, in step S1, the base oil is selected from at least one of polyalphaolefin, alkylnaphthalene, pentaerythritol ester, trimethylolpropane ester, and trimellitate.

[0010] Optionally, in step S1, the mass ratio of the graphene oxide powder, the oily dispersant, the lipophilic modifier and the base oil is 1:(1~5):(2~6):(10~30).

[0011] Optionally, in step S1, the emulsification dispersion I is carried out at a speed of 2000~5000 rpm for 1-3 hours.

[0012] Optionally, in step S1, the temperature of the heat preservation is 0~20℃.

[0013] Optionally, the insulation temperature is any value or a range between 0℃, 2℃, 5℃, 8℃, 10℃, 12℃, 15℃, and 20℃.

[0014] Maintaining a low temperature is to prevent localized modification reactions. Step S1 first forms a graphene oxide suspension system.

[0015] Optionally, in step S2, the hydrophilic modifier comprises at least one amino group with active hydrogen and at least two hydroxyl groups, ester bonds, amide bonds, methoxy groups, oxyvinyl groups, oxypropylene groups, or ethyleneimine groups.

[0016] Optionally, in step S2, the hydrophilic modifier is selected from at least one of diethanolamine, dopamine, 3,4-dimethoxyphenylethylamine, monoethanolamine borate, diethanolamine borate, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, monoamino polyetheramine, diamino polyetheramine, triamino polyetheramine, and amino-terminated dendritic polyamide-amine; Alternatively, the hydrophilic modifier may be prepared by reacting two types of raw materials: one type is an amine compound, and the other type is an active monomer. The amine compound is selected from at least one of ethylenediamine, aminoethylpiperazine, and hydroxyethylethylenediamine, and the active monomer is selected from at least one of glycidol, N-(2-hydroxyethyl)acrylamide, and hydroxyethyl acrylate.

[0017] Optionally, in step S2, the co-solvent is selected from at least one of ethanol, methanol, propanol, and isopropanol.

[0018] Optionally, in step S2, the mass ratio of the graphene oxide powder, water, hydrophilic modifier and cosolvent is 1:(5~10):(2~6):(5~10).

[0019] Optionally, in step S2, the mixing time between the mixture and the suspension is 0.5 to 2 hours.

[0020] Optionally, in step S2, the speed of the emulsification dispersion II is 5000~10000 rpm.

[0021] Optionally, in step S2, the heat preservation temperature of the emulsification dispersion II is 0~20℃.

[0022] Optionally, in step S2, the heating rate is 8~16℃ / h, and the final temperature of the heating is 80~120℃.

[0023] The endpoint temperature of the heating is any value among 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, and 120℃, or a range between any two.

[0024] In step S2, after the mixture is added, the system forms a water-in-oil emulsion. During the heating process, the graphene oxide undergoes an asymmetric modification reaction.

[0025] Optionally, in step S2, the absorbent is added to the slurry and then subjected to vacuum distillation to obtain a purified oily slurry containing asymmetric modified graphene.

[0026] The absorbent is added to consume the residual hydrophilic modifier in the system, and vacuum distillation is used to remove water and co-solvent from the system. The co-solvent can accelerate evaporation.

[0027] Optionally, the absorbent is polyisobutylene succinic anhydride.

[0028] Optionally, the mass ratio of the graphene oxide powder to the absorbent is 1:(1~4).

[0029] Optionally, the stirring speed of the vacuum distillation is 200~500 rpm, the temperature is 80~120℃, and the time is 4~6 h.

[0030] The principle of this preparation method is as follows: A large quantity of graphene oxide powder is dispersed in base oil using an oily dispersant. This results in a low-viscosity graphene oxide suspension system with good fluidity. However, the graphene oxide is not effectively dispersed and does not come into effective contact with the lipophilic modifier, thus the modification reaction does not occur. A small amount of water and co-solvent are added to form a water-in-oil emulsion system. The graphene oxide enters the aqueous phase and achieves good dispersion. At this point, the system maintains good fluidity, equivalent to adding a high-solids-content aqueous dispersion of graphene oxide. Simultaneously, it effectively contacts and reacts with the hydrophilic modifier. Finally, the water and co-solvent are removed. During the formation of the water-in-oil emulsion system, the graphene oxide tends to be distributed at the oil-water interface. The modifier in the oil phase reacts with the groups of graphene oxide facing the oil phase, while the modifier in the aqueous phase reacts with the groups of graphene oxide facing the aqueous phase. Both modification reactions occur simultaneously, ultimately yielding asymmetric modified graphene, which exhibits characteristics similar to a surfactant.

[0031] According to a second aspect of this application, an asymmetric modified graphene for lubricating oil prepared by the method described above is provided.

[0032] A type of asymmetric modified graphene for lubricating oil prepared by the above method, wherein the asymmetric modified graphene uses graphene oxide powder as a sheet matrix, with oleophilic modifying groups grafted onto one side of the graphene oxide sheet and hydrophilic modifying groups grafted onto the other side, and the asymmetric modified graphene has an asymmetric amphiphilic structure with one side being oleophilic and the other side being hydrophilic.

[0033] Optionally, the lipophilic modifying group includes C1-C1 groups. 30 Alkyl and / or C6-C 30 Aryl; The hydrophilic modifying group includes at least one of amino, hydroxyl, ester bond, amide bond, methoxy, oxyvinyl, oxypropylene, and ethyleneimine groups.

[0034] The beneficial effects that this application can produce include: 1. By first constructing a graphene oxide suspension system and then adding a small amount of water to form a water-in-oil emulsion, graphene oxide enters the oil / water interface, achieving graphene oxide dispersion and providing the possibility for modification reactions. This method avoids the addition of a large amount of water and obtains products with high solid content, which is beneficial for production and application.

[0035] 2. By forming a water-in-oil emulsion, both sides of graphene oxide can be modified simultaneously with hydrophilicity and oleophilicity. The process is simple and highly feasible.

[0036] 3. The prepared asymmetric modified graphene has better anti-wear and friction reduction properties. For example, at the lubricating oil (engine oil) / metal interface, the asymmetric modified graphene will move towards the lubricating oil (engine oil) / metal interface, the hydrophilic surface is compatible with the metal, and a friction protective film is quickly formed, which can make the anti-wear and friction reduction properties take effect quickly in the early stage of friction. At the same time, the friction film is relatively stable and not easily damaged.

[0037] 4. The prepared asymmetric modified graphene has better performance in preventing oil burning. For example, at the lubricating oil (engine oil) / air interface (in the engine combustion chamber), the asymmetric modified graphene will move towards the lubricating oil (engine oil) / air interface. The hydrophilic side of the asymmetric modified graphene faces the air and quickly forms a graphene film on the surface of the lubricating oil (engine oil), thereby isolating the air and preventing oil burning. At the same time, due to the presence of modified groups, the graphene film is not compatible with fuel and can isolate the lubricating oil (engine oil) and fuel in a short time, preventing fuel from entering the lubricating oil (engine oil).

[0038] 5. The asymmetric modified graphene obtained has better filter paper permeability and is almost not adsorbed by oil filters, so it can be effective over a longer mileage. Attached Figure Description

[0039] Figure 1-1 The images show the appearance of each group of samples before filtration. Figure 1-2 The images show the appearance of each group of samples after filtration. Among them, 1 corresponds to sample 1#, 2 corresponds to control sample 4#, 3 corresponds to control sample 3#, 4 corresponds to control sample 6#, 5 corresponds to control sample 5#, and 6 corresponds to pure lubricating oil.

[0040] Figure 2 The friction curves for each group of samples are shown.

[0041] Figure 3-1 The image shows the wear scar morphology of sample 1#. Figure 3-2 The image shows the wear scar morphology of pure lubricating oil. Figure 3-3 For comparison, see the wear scar morphology of sample #3; Figure 3-4 For comparison, see the wear scar morphology of sample 4#; Figure 3-5 For comparison, see the wear scar morphology of sample 6#. Detailed Implementation

[0042] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0043] Unless otherwise specified, the raw materials and reagents used in the embodiments of this application were all purchased commercially.

[0044] The graphene oxide powder was purchased from Shandong Lite Nanotechnology Co., Ltd., Changzhou Sixth Element Materials Technology Co., Ltd., or Jiangsu Shanyuan Technology Co., Ltd.

[0045] The lubricating oil was purchased from Guangzhou Bangma Petroleum Technology Co., Ltd.

[0046] Unless otherwise specified, all test methods are standard and all instrument settings are those recommended by the manufacturer.

[0047] In this application, graphene without a prefix (prefixes include oxidation, asymmetric modification, double-sided oleophilic modification, single-sided modification, etc.) is considered unmodified graphene.

[0048] Example 1 S1. Mix 1 part graphene oxide powder (100g), 2 parts boronized polyisobutylene succinimide, 4 parts N-phenyl-1-naphthylamine, and 15 parts PAO-4 thoroughly, disperse in an emulsifier at 3000rpm for 2h, and maintain a low temperature of 10℃ to obtain a graphene oxide suspension.

[0049] S2. Hydroxyethyl ethylenediamine and hydroxyethyl acrylate were added to a mixed solvent of water and isopropanol in a molar ratio of 1:2. The total mass of hydroxyethyl ethylenediamine and hydroxyethyl acrylate was 4 parts, water was 8 parts, and isopropanol was 7 parts. The mixture was reacted at 25°C for 24 hours. The above mixture was gradually added to a suspension of graphene oxide over 1 hour. Emulsification and dispersion were continued at 8000 rpm, and the temperature was gradually increased at a rate of 10°C / hour, with the final temperature reaching 100°C, during which an asymmetric modification reaction occurred.

[0050] S3. Add 2 parts of polyisobutylene succinic anhydride, distill under reduced pressure, stir at 400 rpm, at 100 ℃ for 5 h, to obtain a purified oily slurry containing asymmetric modified graphene, which is designated as sample 1#.

[0051] Example 2 S1. Mix 1 part graphene oxide powder (100g), 3 parts Span 80, 3 parts polyisobutylene succinimide, and 10 parts AN-5 thoroughly, disperse in an emulsifier at 2000rpm for 3h, and maintain a low temperature of 0℃ to obtain a graphene oxide suspension.

[0052] S2. Add aminoethylpiperazine and glycidyl ether to a mixed solvent of water and ethanol at a molar ratio of 1:2. The total mass of aminoethylpiperazine and glycidyl ether is 3 parts, water is 7 parts, and ethanol is 8 parts. React at 30°C for 48 hours. Gradually add the above mixture to a graphene oxide suspension over 0.5 hours, continuing emulsification and dispersion at 7000 rpm. Gradually increase the temperature at a rate of 11°C / h, reaching a final temperature of 110°C, during which an asymmetric modification reaction occurs.

[0053] S3. Add 1 part of polyisobutylene succinic anhydride, distill under reduced pressure, stir at 200 rpm, temperature at 80℃, for 4 hours to obtain a purified oily slurry containing asymmetric modified graphene, denoted as sample 2#.

[0054] Example 3 S1. Mix 1 part graphene oxide powder (100g), 4 parts tallow amine polyoxyethylene ether, 5 parts polyisobutylene amine, and 20 parts pentaerythritol ester PE451 thoroughly, disperse in an emulsifier at 4000rpm for 1h, and maintain a low temperature of 15℃ to obtain a graphene oxide suspension.

[0055] S2. Ethylenediamine and N-(2-hydroxyethyl)acrylamide were added to a mixed solvent of water and n-propanol in a molar ratio of 1:2. The total mass of ethylenediamine and N-(2-hydroxyethyl)acrylamide was 5 parts, water was 9 parts, and n-propanol was 6 parts. The reaction was carried out at 20°C for 36 hours. The above mixture was gradually added to a graphene oxide suspension over 1.5 hours. Emulsification and dispersion were continued at 9000 rpm, and the temperature was gradually increased at a rate of 15°C / hour, with the final temperature reaching 120°C, during which an asymmetric modification reaction occurred.

[0056] S3. Add 3 parts of polyisobutylene succinic anhydride, distill under reduced pressure, stir at 300 rpm, temperature at 90℃, for 6 hours to obtain a purified oily slurry containing asymmetric modified graphene, denoted as sample 3#.

[0057] Comparative Example 1 Compared to Example 1, Comparative Example 1 did not add water. It was mixed with base oil, oily dispersant, and lipophilic modifier and heated. The specific operation was as follows: 1 part of graphene oxide powder (100g), 2 parts of boronized polyisobutylene succinimide, 4 parts of N-phenyl-1-naphthylamine, and 15 parts of PAO-4 were mixed thoroughly and dispersed in an emulsifier at 8000rpm for 6h. The temperature was raised to 100℃ to obtain the product, which was recorded as Comparative Sample 1#. Comparative Sample 1# had a higher fineness, indicating that it was not dispersed. The reaction product system was brownish-black.

[0058] Comparative Example 2 Compared to Example 1, in Comparative Example 2, graphene oxide powder was first dispersed in petroleum ether and ultrasonically dispersed. Then, it was mixed and reacted with base oil, oily dispersant, and lipophilic modifier. Finally, the petroleum ether was removed. The specific operation was as follows: 1 part of graphene oxide powder (100g) was added to 100 parts of petroleum ether and ultrasonically treated. Then, 2 parts of boronized polyisobutylene succinimide, 4 parts of N-phenyl-1-naphthylamine, and 15 parts of PAO-4 were added. The mixture was thoroughly mixed and dispersed in an emulsifier at 8000rpm for 6h. The temperature was raised to 100℃, and the petroleum ether was removed by vacuum distillation during the process. The product was obtained and was designated as Comparative Sample 2#. Comparative Sample 2# had a lower fineness, and the reaction product system was black.

[0059] Comparative Example 3 Compared to Example 1, in Comparative Example 3, graphene oxide powder was first dispersed in water, then mixed and reacted with base oil, oily dispersant, and lipophilic modifier, and then the water was removed. The specific operation was as follows: 1 part of graphene oxide powder (100g) was added to 100 parts of water, ultrasonically treated, then 2 parts of boronized polyisobutylene succinimide, 4 parts of N-phenyl-1-naphthylamine, and 15 parts of PAO-4 were added, mixed thoroughly, dispersed in an emulsifier at 8000rpm for 6h, and heated to 100℃. During the process, water was removed by vacuum distillation to obtain a purified oily slurry containing double-sided lipophilic modified graphene, which was designated as Comparative Sample 3#. The permeability of Comparative Sample 3# was almost the same as that of Sample 1#, but the anti-wear performance was much worse, and there was no significant improvement in preventing oil burning.

[0060] Comparative Example 4 Comparative Example 4, compared to Example 1, did not include a hydrophilic modifier. The specific procedures were as follows: S1, 1 part graphene oxide powder (100g), 2 parts boronized polyisobutylene succinimide, 4 parts N-phenyl-1-naphthylamine, and 15 parts PAO-4 were thoroughly mixed and dispersed at 3000 rpm for 2 hours using an emulsifier, maintaining a low temperature of 10°C to obtain a graphene suspension; S2, a mixture of 8 parts water and 7 parts isopropanol was gradually added to the graphene oxide suspension over a period of 1 hour, and emulsification continued. Disperse at 8000 rpm, gradually increase temperature at a rate of 10℃ / h, and reach a final temperature of 100℃, during which a modification reaction occurs; S3, add 2 parts of polyisobutylene succinic anhydride, distill under reduced pressure, stir at 400 rpm, maintain a temperature of 100℃, and wait for 5 hours to remove water and co-solvent, and obtain a purified oily slurry containing single-sided modified graphene oxide, designated as control sample 4#. Control sample 4# has similar permeability to sample 1#, but its anti-wear performance is slightly worse, and its performance in preventing oil burning is also slightly worse.

[0061] Comparative Example 5 Compared to Comparative Example 1, in Comparative Example 5, the graphene powder was first dispersed in petroleum ether, ultrasonically dispersed, and then mixed and reacted with base oil, oily dispersant, and lipophilic modifier. The petroleum ether was then removed. The specific operation was as follows: 1 part (100g) of graphene with a sheet diameter of 5μm was added to 100 parts of petroleum ether and ultrasonically treated. Then, 2 parts of boronized polyisobutylene succinimide, 4 parts of N-phenyl-1-naphthylamine, and 15 parts of PAO-4 were added. The mixture was thoroughly mixed and dispersed in an emulsifier at 8000rpm for 6h. The temperature was raised to 100℃, and the petroleum ether was removed by vacuum distillation during the process to obtain the product, which was designated as Comparative Sample 5#.

[0062] Comparative Example 6 Compared to Comparative Example 1, in Comparative Example 6, the graphene powder was first dispersed in petroleum ether, ultrasonically dispersed, and then mixed and reacted with base oil, oily dispersant, and lipophilic modifier. The petroleum ether was then removed. The specific operation was as follows: 1 part (100g) of graphene with a sheet diameter of 1μm was added to 100 parts of petroleum ether and ultrasonically treated. Then, 2 parts of boronized polyisobutylene succinimide, 4 parts of N-phenyl-1-naphthylamine, and 15 parts of PAO-4 were added and mixed thoroughly. The mixture was dispersed in an emulsifier at 8000rpm for 6h and heated to 100℃. During the process, the petroleum ether was removed by vacuum distillation to obtain the product, which was designated as Comparative Sample 6#.

[0063] Test Example 1: Fineness Scraper Test The test results of Sample 1# compared to Control Sample 1# and Control Sample 2# show that forming a suspension first and then adding water can achieve the dispersion of graphene oxide. The products of each group were tested using a scraper fineness meter, and the results are shown in Table 1: only Control Sample 1# has a larger fineness, indicating that under this condition, the graphene oxide was not fully dispersed and no modification reaction occurred.

[0064] Table 1

[0065] Test Example 2: Filter Paper Permeability Experiment A commercially available Bosch oil filter was disassembled to obtain its filter paper. Using vacuum filtration, 100ml of each product was collected. The graphene content in the product was 200ppm. The filter was then repeated 20 times. The results are as follows: Figure 1-1 , 1-2 As shown: the colors of sample 1#, control sample 4#, and control sample 3# hardly changed before and after filtration, indicating that the modified graphene was hardly retained by the filter paper; while control sample 6#, control sample 5#, and pure lubricating oil were partially retained by the filter paper during filtration, and the larger the sheet diameter, the greater the retention ratio. That is, the filter paper permeability is: asymmetric modified graphene ≈ single-sided modified graphene oxide ≈ double-sided oleophilic modified graphene >> graphene.

[0066] Test Example 3: Friction Performance Test The products obtained from the examples and comparative examples were added as additives to the finished lubricating oil, and the friction and wear properties of the lubricating oil, including the coefficient of friction and the wear scar diameter, were tested. The finished lubricating oil SP / 0W-30 and finished lubricating oil SP / 0W-30 with added samples 1#, 3#, 4#, and 6# were evaluated using a four-ball friction tester to test their friction reduction and anti-wear properties (industry standard SH / T 0189-92). The test conditions included: GCr15 steel balls, rotation speed 1200 r / min, oil temperature 75℃, long-wear time 60 min, and load 392 N. The data provided by the four-ball friction tester included the wear scar diameter and the coefficient of friction. The smaller the wear scar diameter, the higher the anti-wear ability; the smaller the coefficient of friction, the better the friction reduction performance. Friction curves were also presented. Figure 2 As shown, the morphology of the wear scars is as follows: Figure 3-1 , Figure 3-2 , Figure 3-3 , Figure 3-4 and Figure 3-5 As shown. The friction curve of sample 1# is very flat, indicating that the asymmetric modified graphene formed a stable friction film throughout the friction process. In contrast, the friction curve of sample 3# is similar to that of pure lubricating oil, showing a significant increase in the friction coefficient in the initial stage. This indicates that the double-sided oleophilic modified graphene did not show a significant improvement in friction, because it is no longer considered a sheet structure compared to graphene. The friction curve of sample 4# is relatively flat initially, but fluctuates significantly later, indicating that the single-sided modified graphene oxide formed a friction film in the initial stage of friction, but its stability was poor, and the film was destroyed in the later stage, leading to significant fluctuations in the friction curve. Compared to sample 1#, the friction curve of sample 6# only fluctuated slightly at the end, indicating that graphene has a good friction-reducing effect, but its stability is slightly worse. Sample 1# has a very small wear scar because its friction curve remains at a low level and flat throughout; the others have larger wear scars to varying degrees due to the fluctuations in their friction curves. Therefore, the friction performance is: Sample 1# ≈ Comparative Sample 6# > Comparative Sample 4# > Comparative Sample 3# ≈ Pure Lubricating Oil.

[0067] Test Example 4: Contact Angle Test 4-1 Contact Angle Test of Graphene-Containing Lubricating Oil on Steel Plate Finished lubricating oil SP / 0W-30 and finished lubricating oil SP / 0W-30 with added sample 1#, control sample 3#, control sample 4#, and control sample 6# were dripped onto steel plates, and the contact angle was tested. The results are shown in Table 2.

[0068] 4-2 Gasoline Contact Angle Test with Graphene Sample 1#, control sample 3#, control sample 4#, and control sample 6# were dispersed in petroleum ether and coated onto a steel plate. After the petroleum ether completely evaporated, a graphene film was formed. No. 92 gasoline was then dropped onto the steel plate, and the contact angle was tested. The smaller the contact angle, the better the affinity, and vice versa. The results are shown in Table 2.

[0069] Table 2

[0070] In summary, the contact angles of pure lubricating oil and comparative samples 4# and 6# are basically the same, indicating that single-sided modified graphene oxide and graphene have almost no effect on the interface of lubricating oil. The double-sided oleophilic modified graphene in comparative sample 3# exhibits a certain difference in amphiphilicity at its interface, which can moderately improve the interfacial affinity of lubricating oil. After double-sided asymmetric modification, the asymmetric modified graphene in sample 1# shows significant differences in hydrophilic and oleophilic properties on both sides, allowing it to be directionally arranged and enriched in the lubricating oil system, with the hydrophilic side facing outwards. This effectively changes the wetting affinity of lubricating oil to different interfaces, showing a significant increase in affinity for metal interfaces and a significant decrease in affinity for gasoline. Furthermore, the hydrophilicity regulation ability of double-sided asymmetric modified graphene is far superior to that of single-sided modified, double-sided oleophilic modified, and unmodified graphene, further enhancing the affinity for metal interfaces and further weakening the affinity for gasoline. This trend is consistent with the results of friction performance testing and oil burning testing.

[0071] Test Example 5: Oil Consumption Test A 10-year-old Nissan Sylphy classic sedan (with severe oil consumption) was selected as the test subject. The test route was an urban elevated road, and the test time was during rush hour. Real-world oil consumption tests were conducted on finished lubricating oil SP / 0W-30 and finished lubricating oil SP / 0W-30 with samples 1#, 3#, 4#, 5#, and 6# added respectively. The engine was cleaned before each oil change, and the amount of oil added was controlled to 3 liters. The test mileage for each lubricating oil was about 1000 kilometers. The degree of oil consumption was judged by the amount of oil remaining. The results are shown in Table 3.

[0072] Table 3

[0073] In summary, this vehicle suffers from severe oil consumption. Adding either graphene or modified graphene significantly suppresses this problem, with single-sided modified graphene oxide and double-sided asymmetric modified graphene showing particularly pronounced effects. This is because graphene / modified graphene possesses flame-retardant properties. Graphene / modified graphene is uniformly distributed in the lubricating oil. In the combustion chamber, lubricating oil combustion primarily occurs at the lubricating oil-air interface. Fuel dissolving into the lubricating oil, lowering its ignition point, is one contributing factor to combustion. However, due to the presence of graphene / modified graphene, after the lubricating oil between the air and the graphene / modified graphene is burned off, the graphene / modified graphene is exposed to the air, thus preventing further combustion. Especially for single-sided modified graphene oxide and double-sided asymmetric modified graphene, both migrate towards the lubricating oil-air interface, preventing fuel from dissolving into the lubricating oil, thereby exhibiting a significant effect in suppressing oil consumption. On the other hand, graphene is less effective at inhibiting oil consumption than modified graphene because it can be adsorbed by the filter element of the oil filter. In particular, graphene with larger flake diameters is more easily adsorbed, and its effect on inhibiting oil consumption is lower than that of graphene with smaller flake diameters.

[0074] Test Example 6: Dispersion Stability Modified graphene was added to the finished lubricating oil GL-5 85W-140 at a weight ratio of 100 ppm and dispersed by manual stirring. The mixture was centrifuged at 1440g (1440 times the acceleration due to gravity) for 30 minutes (approximately equivalent to one month of natural settling), paused for 30 minutes, and then centrifuged again for 30 minutes. This process was repeated for a total of 4 hours. The resulting structures are shown in Table 4.

[0075] Table 4

[0076] In summary, modified graphene exhibits significantly better dispersion stability in lubricating oils than graphene. Among them, single-sided modified graphene oxide and double-sided asymmetric modified graphene are slightly worse than double-sided oleophilic modified graphene, but the difference is not significant.

[0077] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing asymmetric modified graphene for lubricating oil, characterized in that, The preparation method includes the following steps: S1. Mix graphene oxide powder, oily dispersant, lipophilic modifier and base oil, emulsify and disperse I, keep warm to obtain graphene oxide suspension; S2. A mixture containing water, a hydrophilic modifier, and a co-solvent is mixed with a suspension, emulsified and dispersed (II), heated, and reacted to obtain a slurry containing asymmetric modified graphene.

2. The preparation method according to claim 1, characterized in that, In step S1, the oily dispersant is selected from at least one of Span 80, boronized polyisobutylene succinimide, isopropyl titanate, dehydrated sorbitan oleate, polyether, stearic acid, oleic acid, and tallow amine polyoxyethylene ether. Preferably, in step S1, the lipophilic modifier is selected from at least one of tallow amine, polyisobutylene amine, polyisobutylene succinimide, butyl diphenylamine, octyl diphenylamine, nonyl diphenylamine, and N-phenyl-1-naphthylamine; Preferably, in step S1, the base oil is selected from at least one of polyalphaolefin, alkylnaphthalene, pentaerythritol ester, trimethylolpropane ester, and trimellitate.

3. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of the graphene oxide powder, the oily dispersant, the lipophilic modifier and the base oil is 1:(1~5):(2~6):(10~30).

4. The preparation method according to claim 1, characterized in that, In step S1, the emulsification dispersion I is carried out at a speed of 2000~5000 rpm for 1-3 hours. Preferably, in step S1, the temperature of the heat preservation is 0~20℃.

5. The preparation method according to claim 1, characterized in that, In step S2, the hydrophilic modifier comprises at least one amino group with active hydrogen and at least two hydroxyl groups, ester bonds, amide bonds, methoxy groups, oxyvinyl groups, oxypropylene groups, or ethyleneimine groups; Preferably, in step S2, the hydrophilic modifier is selected from at least one of diethanolamine, dopamine, 3,4-dimethoxyphenylethylamine, monoethanolamine borate, diethanolamine borate, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, monoamino polyetheramine, diamino polyetheramine, triamino polyetheramine, and amino-terminated dendritic polyamide-amine; Alternatively, the hydrophilic modifier may be prepared by reacting two types of raw materials, one type being an amine compound and the other being an active monomer, wherein the amine compound is selected from at least one of ethylenediamine, aminoethylpiperazine, and hydroxyethylethylenediamine, and the active monomer is selected from at least one of glycidol, N-(2-hydroxyethyl)acrylamide, and hydroxyethyl acrylate; Preferably, in step S2, the co-solvent is selected from at least one of ethanol, methanol, propanol, and isopropanol.

6. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of the graphene oxide powder, water, hydrophilic modifier and cosolvent is 1:(5~10):(2~6):(5~10).

7. The preparation method according to claim 1, characterized in that, In step S2, the mixing time between the mixture and the suspension is 0.5 to 2 hours. Preferably, in step S2, the speed of the emulsification dispersion II is 5000~10000 rpm; Preferably, in step S2, the heat preservation temperature of the emulsification dispersion II is 0~20℃; Preferably, in step S2, the heating rate is 8~16℃ / h, and the final temperature of the heating is 80~120℃.

8. The preparation method according to claim 1, characterized in that, In step S2, the absorbent is added to the slurry, and then vacuum distillation is performed to obtain a purified oily slurry containing asymmetric modified graphene.

9. The preparation method according to claim 8, characterized in that, The absorbent is polyisobutylene succinic anhydride; Preferably, the mass ratio of the graphene oxide powder to the absorbent is 1:(1~4). Preferably, the stirring speed of the vacuum distillation is 200~500 rpm, the temperature is 80~120℃, and the time is 4~6 h.

10. An asymmetric modified graphene for lubricating oil prepared by the method according to any one of claims 1 to 9, characterized in that, The asymmetric modified graphene uses graphene oxide powder as the sheet matrix. One side of the graphene oxide sheet is grafted with oleophilic modifying groups, and the other side is grafted with hydrophilic modifying groups. The asymmetric modified graphene has an asymmetric amphiphilic structure with one side being oleophilic and the other side being hydrophilic.